2007
DOI: 10.1177/00222194070400010601
|View full text |Cite
|
Sign up to set email alerts
|

Locus and Nature of Perceptual Phonological Deficit in Spanish Children With Reading Disabilities

Abstract: The aims of this study were (a) to determine whether Spanish children with reading disabilities (RD) show a speech perception deficit and (b) to explore the locus and nature of this perceptive deficit. A group of 29 children with RD, 41 chronological age-matched controls, and 27 reading ability-matched younger controls were tested on tasks of speech perception. The effect of linguistic unit (word vs. syllable) and type of phonetic contrast (voicing, place and manner of articulation) were analyzed in terms of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
8

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 76 publications
0
7
0
8
Order By: Relevance
“…A dificuldade na descoberta do princípio fonológico (identificação e manipulação de fonemas) ocasiona problemas de leitura no sistema de escrita alfabética 8,16,31 . Desta forma, o que este estudo evidenciou é que as crianças com dislexia do desenvolvimento apresentaram dificuldades quanto à identificação de rima e produção de palavras com o som dado, apontando para um déficit em acessar os códigos fonológicos, representações fonológicas e de armazenamento fonológico 4,28,[31][32][33] . O teste de rima envolve a identificação de unidades chamadas intra-sílabas e é realizado a partir da detecção de dois fonemas comuns.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…A dificuldade na descoberta do princípio fonológico (identificação e manipulação de fonemas) ocasiona problemas de leitura no sistema de escrita alfabética 8,16,31 . Desta forma, o que este estudo evidenciou é que as crianças com dislexia do desenvolvimento apresentaram dificuldades quanto à identificação de rima e produção de palavras com o som dado, apontando para um déficit em acessar os códigos fonológicos, representações fonológicas e de armazenamento fonológico 4,28,[31][32][33] . O teste de rima envolve a identificação de unidades chamadas intra-sílabas e é realizado a partir da detecção de dois fonemas comuns.…”
Section: Discussionunclassified
“…A consciência de que a lín-gua é composta de pequenos sons é fundamental para aprender a ler e produzir a escrita alfabética. A proficiência em decodificação de palavras em segmentos menores tem relação com melhor desempenho futuro em leitura [1][2][3][4] . O sistema alfabético de escrita associa um componente auditivo fonêmico a um componente visual gráfico (correspondência grafofonêmica) e para a compreensão do princípio alfabético são necessá-rios três fatores: a consciência de que é possível segmentar a língua falada em unidades distintas; o conhecimento de que essas mesmas unidades repetem-se em diferentes palavras faladas e a ciên-cia das regras de correspondência entre grafemas e fonemas.…”
Section: Desempenho De Escolares Com Dislexia Do Desenvolvimento Em Tunclassified
“…Because reading acquisition requires the child to learn the phoneme-grapheme correspondences, problems with phonological information lead to difficulties in reading acquisition. Different studies carried out in the Spanish language using reading-age-and chronological-age-matched designs have also found a deficit in phonological awareness in children with dyslexia [25,26,[30][31][32][33][34]. However, some studies [34][35][36] have shown that the origin of this phonological deficit is a deficit in speech perception, as they also found temporal-processing problems in speech perception in children with dyslexia [35].…”
Section: Reading-related Cognitive Deficits In Dyslexia and Emotionalmentioning
confidence: 99%
“…Speech perception has been investigated in children of different ages with and without dyslexia [31][32][33][34]. Ref.…”
Section: Speech Perceptionmentioning
confidence: 99%
“…Some studies have found that deficits in phonetic discrimination produce errors in phonological representations of the lexicon, and therefore in phonological decodification [32][33][34]. Thus, readers with dyslexia present deficits in phonological processes due to difficulty creating phonological representations based on acoustic signals of speech [32].…”
Section: Speech Perceptionmentioning
confidence: 99%